A Systematic Review and Meta-Analysis Protocol of Chemoablation vs. Transurethral Resection of Bladder Tumor in Patients With Non-Muscle-Invasive Bladder Cancer - Xu Shi (Frontiers Media S.A., 2021)
Background: Bladder cancer is the second-ranked tumor of the genitourinary system. Transurethral resection of bladder tumor (TURBT) is currently the most important diagnosis and treatment method for non-muscular invasive bladder cancer (NMIBC). However, due to its high recurrence and progression rate, as well as high cost and inapplicability to some patients, intravesical chemoablation as an alternative to TURBT may be promising for NMIBC patients. However, there are very little data comparing its effectiveness, safety, best effective drug type, dosage selection, and cost with TURBT at present, which deserves further evaluation. The present study was designed in order to discuss which treatment is superior to another between chemoablation and TURBT in patients with NMIBC.Methods and Analysis: Databases including PubMed, MEDLINE, EMBASE, and Cochrane Library databases, as well as Chinese databases including CNKI (China national knowledge infrastructure), Wan Fang database, and Chinese Clinical Trial Registry, from August 1994 to the time when the official submission of this review was published was included in this review and screened by two reviewers (XS and DCF) independently. There were no language limitations. The study was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Data was analyzed using RevMan and Stata software. The primary aims were the clinical effectiveness, including response rate, complete response OS, CSM, recurrence rate, time to recurrent, progression rate, and time to progression, among others. The secondary aims mainly included safety and tolerability, including costs, operation time, hospital stay, bleeding volume, and complications, among others.Study Registration: This study is registered as PROSPERO CRD42021271124.